Estimation of Origin-Destination Trip Matrices for Small Cities - Novačko, Luka; Šimunović, Ljupko; Krasić, Davor (Promet - Traffic&Transportation, 2014)
This paper presents a model of data assessment for the requirements of a classical four-step model of traffic demand in individual traffic in small cities. The procedure is carried out by creating an initial origin-destination trip matrix using data from the traffic count and by defining the average rate of trip generation within single households. The research applied fuzzy logic for the correction of the initial trip matrix. The paper also presents the recommendations for defining the borders of traffic zones, as well as the locations of traffic counts. A flowchart has been used to show a summarized presentation of the proposed model. In the last part of the paper the model was tested on an example of a smaller city in the Republic of Croatia.